STRATEGI PENGENDALIAN PAPAYA RINGSPOT VIRUS (PRSV) PENYEBAB PENYAKIT BERCAK BERCINCIN PADA PEPAYA - Temaja, I Gede Rai Maya; Sudiarta, I Putu; Darmiati, Ni Nengah; Puspawati, Ni Made (Journal of Agricultural Science and Biotechnology; Vol 5 No 1 (2016), 2016)
ELISA test results of symptomatic leaves from Tabanan, Bali showed that papaya ringspot virus (PRSV) as causing agents of ring spot disease on papaya in Bali. The objective of the study were to determine the control strategies of ringspot disease on papaya in the field. Control strategies of ringspot disease tested in this study were the use of metallic gray plastic mulch and plant barrier. Research result showed that plant barrier can provide a buffer zone to protect papaya that are planted within the confines of the buffer.
Keywords: ringspot disease, papaya ringspot virus (PRSV), vector, host range